Functional role of hedgehog pathway in osteoarthritis. (12th December 2019) - Xiao, Wen‐feng; Li, Yu‐sheng; Deng, Ang; Yang, Yun‐tao; He, Miao
Abstract : The hedgehog signalling pathway is one of the key regulators of metazoan development, and it plays an important role in the regulation of a variety of developmental and physiological processes. But it is aberrantly activated in many human diseases, including osteoarthritis (OA). In this study, we have reviewed the association of hedgehog signalling pathway in the development and progression of OA and evaluated the efforts to target this pathway for the prevention of OA. Usually in OA, activation of hedgehog induces up‐regulation of the expression of hypertrophic markers, including type X collagen, increases production of nitric oxide and prostaglandin E2, several matrix‐degrading enzymes including matrix metalloproteinase and a disintegrin and metalloproteinase with thrombospondin motifs in human knee joint cartilage leading to cartilage degeneration, and thus contributes in OA. Targeting hedgehog signalling might be a viable strategy to prevent or treat OA. Chemical inhibitors of hedgehog signalling is promising, but they cause severe side effects. Knockdown of HH gene is not an option for OA treatment in humans because it is not possible to delete HH in larger animals. Efficient knockdown of HH achieved by local delivery of small interfering RNA in future studies utilizing large animal OA models might be a more efficient approach for the prevention of OA. However, it remains a major problem to develop one single scaffold due to the different physiological functions of cartilage and subchondral bones possess. More studies are necessary to identify selective inhibitors for efficiently targeting the hedgehog pathway in clinical conditions.